Città e agricoltura periurbana: la traiettoria francese - Bonnefoy, Serge (Scienze del Territorio, 2014)
The paper aims at retracing the steps of peri-urban agriculture in France. Starting from the history of dualism between Town and Country, and highlighting the periurban agriculture’s phases of politicization, it deals with the issue of development of agglomeration policies in which the agriculture topic is embedded, leading to the emergence of five different types of agricultural agglomeration policies. It describes the great movements which, today, are deeply renewing peri-urban agriculture policies: the identification of sustainable cities (together with the fight against urban sprawl), the food issue (with the enhancement of the production function of agriculture) and the return to a territorial economy. The focus is then placed on the uncertainty of the argument and its exploitation by different policies.